To Study the Effect of Gender and Faculty of Aptitude and Achievement in English: Analyzing Gender Gaps in Academic Achievement among 10th Grade Students in Tamil Nadu (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Gender issues have been the subject of today's educational platform. While the literacy rate is higher among boys than girls, it is important to notice that girls are better off than boys in nearly all academic other competitive exams. Academic achievement is perceived to be a crucial parameter for determining one's overall ability and capability. In this study analysis, the researcher studied and measured the gender gaps in the academic performance of the 10th grade students in the Salem Sankari education districts of Tamil Nadu. The Ex-post Facto test approach was introduced in this review annual exam marks earned by students (N=195,941 Boys-1,02,027 and Girls-93,914) in English in the last five years (2007-2011) were utilized as a metric to evaluate academic achievement.